2018
DOI: 10.1007/s13224-018-1134-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sleep-Disordered Breathing on Severity of Pregnancy-Induced Hypertension and Feto-Maternal Outcomes

Abstract: Background There is a close association between sleepdisordered breathing (SDB) and preeclampsia. Both conditions have poor pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Researchers often used eligible questionnaires to diagnose OSA in pregnancy, validated as a screening tool in non-pregnant populations. Most of the authors in this study utilized the BQ, which concentrated on self-reported snoring and apnea [ 40 , 42 , 43 , 49 , 50 , 55 , 56 ]. It has a sensitivity of 86% and a specificity of 77% in non-pregnant adults [ 22 ], while it only had a sensitivity and specificity of 35% and 63.8%, respectively, in pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers often used eligible questionnaires to diagnose OSA in pregnancy, validated as a screening tool in non-pregnant populations. Most of the authors in this study utilized the BQ, which concentrated on self-reported snoring and apnea [ 40 , 42 , 43 , 49 , 50 , 55 , 56 ]. It has a sensitivity of 86% and a specificity of 77% in non-pregnant adults [ 22 ], while it only had a sensitivity and specificity of 35% and 63.8%, respectively, in pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the "thrifty phenotype" hypothesis described by Hales and Barker (Suri, Suri, Arora, Gupta, & Adhikari, 2019), gestational environmental exposures, such as gestational hyperglycaemia, maternal obesity and overfeeding or underfeeding during pregnancy, are suggested to epigenetically alter the programming of genes, resulting in a long-term imprint on gene expression (Gluckman, Hanson, & Low, 2011;Godfrey, Inskip, & Hanson, 2011;Hanson, Godfrey, Lillycrop, Burdge, & Gluckman, 2011;Khalyfa et al, 2014).…”
Section: Consequences Of Gestational Sleep Apnea In the Offspringmentioning
confidence: 85%
“…However, there is substantial evidence that people with hypertensive disorders of pregnancy are at higher risk of OSA. 7,[9][10][11]23,[42][43][44][45][46][47][48][49] As a result of the onset of preeclampsia's proximity to the timing of delivery, it is impractical to recommend that people diagnosed with preeclampsia get screened for OSA.…”
Section: Screening For Osa In Pregnant Peoplementioning
confidence: 99%